Application of Fusion sample preparation X Ray Fluorescence Spectrometry in the Identification of Solid Waste Characteristic of Imported Coated Fibre Cloth. Issue 1 (May 2020) - Luo, Chuan; Wang, Qian; Liu, Zhihong; Wang, Hao; Chen, Tieshan; Lin, Zhenxing
Abstract: The composition of imported coated fibre cloth was quickly identified by fusion sample preparation X-ray fluorescence spectrometry. Na2 O, MgO, Al2 O3, SiO2, P2 O5, SO3, K2 O, CaO, TiO2, Cr2 O3, MnO, Fe2 O3, NiO, CuO, ZnO, As2 O3, SrO, ZrO, CdO, BaO, PbO in the matrix of the coated fibre cloth were determined. In this paper, the technology of direct melting of flake sample is studied. The method of pre-oxidation is that the sample piece is obliquely placed on the inner wall of crucible to increase the air circulation space and remove the organic matter and halide in a short time. The 66.5:33.5 mixed flux was used as the flux, and LiBr was used as the release agent. The temperature was about 1050 °C, and the time was about 17 min. The problem of melting of inorganic fibre and flux melt was found and solved. The calibration curve is constructed by silicate rock, bauxite, cement and other reference materials and high-purity reagents. The matrix effect correction adopts the variable theoretical α influence coefficient method, and B2 O3 represents the unmeasured components as the elimination item. The maximum Al2 O3, SiO2, CaO curves of this method are 84.4%, 91.5%, 62.6%, respectively. The Cr, Ni, Cu, As, Cd, Pb curve range of harmful elements is greater than 0.005%-0.33%; 21 curves have good linearity. R 2 divided by BaO equals 0.997 and the rest are greater than 0.9993; the detection limit of harmful elements is less than 15 mg·g −1 ; precision relative standard deviation (n=11) principal component is less than 0.5%, and trace component is less than 15%; after comparison of standard substances and standard methods, the results are consistent. Accuracy of methods is good, and it can quickly identify the content of the main elements of the coated fibre cloth and provide a strong support for the subsequent identification of solid waste characteristic.